Educação infantil: ludicidade no eixo da matemática - SANTOS, Maria José Taveira dos (2022)
The ludic is a tool for the teaching process in the classroom, and this work aims to make an approach on the ludic activities, geared to the axis of mathematics. The methodology of this work is structured in bibliographical research, aiming to describe about the lack of interest and the difficulty of learning of the students by the discipline of Mathematics is a constant complaint among the teachers, and for them, the mathematics classes are nothing more than mere transmissions of formulas, definitions, concepts and results that do not have the least meaning, because the focus of the learning process is the student and for this learning to happen you need to arouse your interest. Thus, in this research, the game will be the starting point to prepare the student to deal with abstract questions that require reflection beyond the elaboration of strategies and solutions to the problems situations from kindergarten to high school, for the above, I reaffirm the relevance of the work done, seeking a better understanding of the use of the game in the classroom, so that in the future, I can make use of this activity in the right way, making the most of its use. The Pedagogical Political Project is support support in the educational process, the introduction of playful pedagogical practices enables an excellent development of student learning.